Reduction of Mutual Coupling and Cross‐Polarization of Microstrip MIMO Antenna Using Electromagnetic Soft Surface (EMSS). Issue 5 (19th May 2022) - Bhattacharjee, Swati; Mandal, Santimoy; Ghosh, Chandan Kumar; Banerjee, Soumen
Abstract: Mutual coupling, in case of closely spaced microstrip antenna elements, is an inevitable phenomenon degrading antenna performances like gain, radiation pattern, return loss, radiation efficiency, etc. In this paper, an approach toward the suppression of mutual coupling between two closely spaced microstrip radiators is presented for the proposed Multiple‐Input‐Multiple‐Output (MIMO) antennas. The same has been materialized through an insertion of a properly designed Electromagnetic Soft Surface structure between the radiating elements, which acts as an electrical wall between two rectangular patches and reduces the mutual coupling up to 50 dB at resonant frequency of 4.35 GHz. An attempt toward reduction of cross‐polarization by 12.5 dB is also achieved with a gain of 5.4 dBi for the proposed antenna. The center‐to‐center spacing between the antenna elements is kept at 22.1 mm (0.32 λ ). The proposed MIMO antenna structure will be useful in case of radar‐ and satellite‐based communication systems. Plain Language Summary: Mutual coupling is an inherent characteristic which may exists in many antenna arrays. For two rectangular microstrip patches, the mutual coupling depends on the relative alignment, separation and geometry of antenna elements. Depending upon element position it is said to be E‐plane, when the elements are collinear to the E‐plane and H‐plane, when the elements are collinear to the H‐plane. The E‐plane produces smallest coupling isolation for small spacing while the H‐plane exhibits the smallest coupling isolation for large edge to edge separation. Key Points: Electromagnetic Soft Surface is applicable for mutual coupling reduction as well as cross‐polarization (XP) reduction The mutual coupling reduction of the proposed antenna is 50 dB, and it achieved a gain of 5.4 dBi The final antenna reduces a XP of about 12.5 dB at the resonant frequency of 4.35 GHz